OPTIMALISASI PEMANFAATAN DANA ZIS DALAM UPAYA MENGEMBANGKAN UMKM MUSTAHIK PADA LAZISMU GRESIK - Litania Nesesita; Mochammad Khoirul Anwar (ITB AAS Indonesia Surakarta, 2023)
Economic recovery has begun after the covid-19 pandemic, there was an economic recovery, but in some areas there was still an increase in the poverty rate, one of which was the Gresik Regency area, so the economic recovery in Gresik was still not improving. Gresik Regency has disseminated information about BPUM funds, but several business owners use the assistance obtained to meet daily needs rather than for business needs and many business do not practice good financial management. This study aims to analyze the optimization of the utilization of ZIS funds at LAZISMU Gresik in an effort to develop mustahik MSMEs and investigate the impact received by mustahik after receiving assistance. This research uses a descriptive qualitativ approach. The results of this study are that LAZISMU Gresik's efforts to develop Mustahik MSMEs are still not optimal, but the impact of mustahik is helped in their business facilities that have been assisted. This research is expected to be a review for LAZISMU Gresik to redesign and for readers it is hoped that there is no need to hesitate in giving charity because there is a charity manager to be distributed to those in need.